PERENCANAAN STRATEGI TI DAN PENERAPANNYA PADA KOMISI AKREDITASI RUMAH SAKIT - Karina Djunaidi (KILAT, 2015)
Commission on Accreditation of Hospitals (KARS) is an independent institution on assessment of the hospital as well as providing a recognition that will be given by the government on the management of the hospital , because it has met the standards set . In improving the international standard accreditation system should also be done on the development of information technology systems in order to tune and support business processes . In the development of Information Technology Systems required a strategic planning and information technology systems development as outlined in the IT Strategic Plan document. By combining the analysis method Strength, Weakness, Opportunity, Threat (SWOT), Critical Success Factor, External Environmental Analysis, Internal Environmental Analysis and IT Balanced Scorecard can produce a strategic plan for the development of information technology described in the KARS’s IT Strategic Plan document. The results of the strategic planning of information technology systems are KARS strategic planning document in the development of information technology so as to enhance the international accreditation standards, improve business processes and gain recognition from the International Society for Quality in Healthcare (ISQua) as an institution of international healthcare accreditation assessor.